1986
DOI: 10.1002/cyto.990070405
|View full text |Cite
|
Sign up to set email alerts
|

DNA and nuclear protein measurement in isolated nuclei of human endometrium

Abstract: Feulgen-DNA and nuclear light green-protein measurements have been performed in isolated nuclei of normal (nonmalignant) and malignant human endometrial homogenates.The DNA content of the GO/Gl fraction of malignant endometrium showed much overlap with that of normal endometrium, or was slightly increased. Two of the 18 carcinomas were clearly aneuploid. No correlation was found between the histological grade and the DNA content. The tumors of clinical stage I1 and higher all had a higher DNA content than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
3
5
1
Order By: Relevance
“…The clinically more advanced carcinomas do not show an increased proliferative activity compared to that of the other carcinomas. These results closely agree with those found in our previous study (11).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The clinically more advanced carcinomas do not show an increased proliferative activity compared to that of the other carcinomas. These results closely agree with those found in our previous study (11).…”
Section: Resultssupporting
confidence: 94%
“…Also, within the malignant population, no indication could be found that suggested a correlation with the histological grade or clinical stage. These results are somewhat different from those obtained in o w previous study (11). In that study, a complete overlap of the nuclear protein content of normal and malignant endometrium was also found.…”
Section: Iiiscussioncontrasting
confidence: 99%
“…In a previous study (14) using image cytometry, we found that with features deduced from the total amount of DNA (integrated optical density of the DNA dye) some differences among endometrial stages could be detected. However, a considerable overlap was still noted.…”
mentioning
confidence: 85%
“…Nuclear isolation and deposition of the nuclei on slides have been extensively described elsewhere (14). In brief, nuclei were prepared by homogenization of the defrosted tissue and fixed in suspension in a methanol:37% forma1dehyde:acetic acid mixture (85:10:5 by volume).…”
Section: Nuclear Isolation and Stainingmentioning
confidence: 99%
“…The use of tissue grinders with tight‐fitting pestles and cold sucrose solutions have a long history of use in the isolation of intact nuclei from rat tissues such as liver (Schneider, 1948; Wilbur & Anderson, 1951) and skeletal muscle (Edelman et al , 1965). Although not mentioned in protocols of sample preparation for FCM DNA analysis (Vindeløv et al , 1983; Petersen, 1985; Ormerod, 2000; Gomez et al , 2001; El‐Naggar & Vielh, 2004; Heinlein et al , 2010), the use of tissue grinders has been reported for DNA analysis of human tumours and cell lines in a few studies (Piwnicka et al , 1983; Oud et al , 1986; Remvikos et al , 1988). High‐density sucrose solution for tissue dissociation reportedly aids to split gap and tight junctions responsible for cell clusters while inclusion of sodium citrate aids to loosen intercellular bonds by sequestrating cations (Ca 2+ and Mg 2+ ) responsible for cell surface and intercellular structural matrix integrity (Pallavicini, 1987).…”
Section: Discussionmentioning
confidence: 99%